THE COMMON NATIONAL CURRICULAR BASIS AS A FAIR EDUCATIONAL POLICY: IMPLEMENTATION OF A FAIR EDUCATION UNDER THE BIAS OF THE DEVELOPMENT OF SKILLS AND COMPETENCES - Arnhold, Débora Tais; Lorenz Martin, Rosemari (Revista Gênero e Interdisciplinaridade, 2021)
The present study seeks to discuss the implementation of the Common National Curriculum Base as an equitable educational policy, presupposing the realization of a fair education under the bias of the development of skills and competences. It also contemplates the concept of principle of equality as one of the greatest concerns of modern capitalist society, besides problematizing the dissemination of knowledge as a force of divergence that acts in Brazilian social inequality. Thus, from a theoretical-practical but also reflexive discussion, we seek to present some problematizations involving the constitution of the current society and a utopian Brazilian educational reality: a quality equitable education that seeks to reduce social inequality.